Framing Intelligent Transport Systems in the Arctic: Reindeer, Fish and the Engineered Road. Issue 1 (2nd January 2023) - Haugland, Bård Torvetjønn; Ryghaug, Marianne; Søraa, Roger Andre
Abstract : The article explores the relationship between humans and other animals, technology, and engineering practices in a project testing Intelligent Transport Systems (ITS) in the arctic. Generally, roads are engineered to promote efficiency and predictability for transport. However, in the arctic northern region of Norway, animals sometimes challenge these virtues. Using Goffman's notion of frames and Callon's concept of overflow as theoretical starting points, the article explores how transport engineers develop intelligent transport infrastructure and envision ways of including animals and other non-humans in the engineers' framing of the road. The engineers first and foremost implement new technological artefacts, which allow them to survey the road in a manner which makes nature's overflows onto the road more manageable. However, these artefacts do not merely contain nature in the engineers' frame—the engineers also envision humans, in this case, motorists, to change their practices. As such, the engineers' attempts to contain animals in a particular frame entail using technology to assemble a new relationship between nature and culture. Taking nature into account when planning and developing infrastructure means reassembling a particular nature-culture relationship. Thus, the article points out that in order to engineer nature, it is also necessary to engineer culture.